Review on the Synthesis and Properties of the Energetic Compound Containing Boron - Wang, Guodong; Suming, Jing; Liu, Guoqing; Gao, Xingyong (Current Organic Chemistry, 2020)
Boron possesses the second greatest heating value of any element that can be adopted as an energetic material in the processing of propellants and explosives. It has become the first choice as a high energy fuel for solid fuel-rich propellants because of its advantages of high theoretical combustion heat. In the actual condition, the combustion efficiency of boron-containing fuel-rich propellants is low, and the potential energy of boron cannot be fully utilized. The compound containing-boron can be used as a new way to improve the combustion efficiency of fuel-rich propellants. In this paper, the progress in the synthesis of energetic borides is reviewed from the perspectives of molecular design, synthesis strategy and route optimization. The situation of the synthesis methods of energetic borides (nitrogen-rich boron esters, poly(azole)borates, nitroboranes, nitrogen-rich borazines and azide boron compounds) is reviewed. The research focus and development trend of various boron compounds are analyzed, and the potential application prospect in the propellant is investigated.
Keywords: Boron